Pelanggaran Kode Etik Hakim dalam Penanganan Perkara: Studi Fenomena dan Dampaknya terhadap Kepercayaan Publik - Muhammad Faisal Firdaus; Ahmad Haikal Manggabarani; Darian Ezra 'Aabidah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Violations of the code of ethics by judges in handling cases constitute a serious problem in the Indonesian judicial system, potentially undermining the integrity of the judiciary. Judges, as key actors in the law enforcement process, are required to uphold the principles of independence, impartiality, and professionalism in every decision they make. However, in practice, various violations persist, such as conflicts of interest, bribery, and abuse of authority. This study aims to analyze the forms of violations of the code of ethics by judges, the factors causing them, and their impact on public trust in the judiciary. The method used is a normative juridical approach by examining laws and regulations, the code of ethics for judges, and relevant case studies. The results indicate that weak oversight, low individual integrity, and external intervention are the main factors contributing to these violations. The resulting impact not only undermines public trust but also undermines the legitimacy of law and justice in society. Therefore, strengthening the oversight system, enforcing strict sanctions, and increasing awareness of professional ethics are necessary to maintain the dignity of the judiciary.